Irritable Bowel Syndrome: A Hallmark of Psychological Distress in Women? - Giuseppe Marano; Gianandrea Traversi; Roberto Pola; Antonio Gasbarrini; Eleonora Gaetani; Marianna Mazza (Life)
Irritable bowel syndrome (IBS) is a functional gastrointestinal disorder characterized by abdominal pain, bloating, and altered bowel habits. Women are disproportionately affected by IBS due to a complex interplay between genetic, environmental, and psychosocial factors, along with a crucial role of the gut–brain axis in modulating both bowel function and pain perception. Evidence suggests a strong association between psychological distress and IBS symptoms. Women with IBS report higher levels of psychological distress compared to men, and sex is a biological variable that shapes several aspects of the mechanisms, epidemiology, and clinical manifestations of IBS. This paper explores the bidirectional relationship between psychological factors and IBS with a focus on women. Stress, anxiety, depression, and childhood trauma contribute to IBS symptomatology, and societal and biological factors unique to women may exacerbate this condition. Strategies for integrated care approaches and gender-specific treatment strategies to improve patient outcomes and quality of life are needed.